The Use of Advance Organizer in Teaching Reading Narrative Text at Eight Grade SMP PGRI Wringinanom - Nur Kalim (PGRI Provinsi Jawa Timur, 2021)
The advance organizer model is designed to strengthen students’ cognitive structures and their knowledge of certain subjects and how to manage, clarify, pay attention and maintain. This study was aimed to describe implementation of advance organizer technique in teaching reading English narrative text at SMP PGRI Wringinanom and the students’ response of the implementation of Advance Organizer technique in teaching reading English narrative text at SMP PGRI Wringinanom. This study applied descriptive qualitative method. The subjects of this research are a teacher and students of A VIII class of junior high school PGRI Wringinanom, Gresik in the academic year 2020/2021. The instruments of this study were the researcher, the observation field note, and questionaire. The data collection procedures in this study were observation and questionnaire. The steps of data analysis were observation and questionaire. The results of this study showed that the advence organizer technique was succesfully implemented. This method had both advantages and disadvanages. Based on students’ responses, the advance organizer is an interesting method that can be applied in teaching English especially Narrative text.